Preparation method and application of nickel disulfide / copper sulfide / carbon composite hollow sphere

Ni-MOF was synthesized by solvothermal method and combined with ion exchange, dopamine and glucose coating, and carbonization and vulcanization to prepare nickel disulfide/cubicide/carbon composite hollow spheres, which solved the volume change and conductivity problems of nickel disulfide in sodium ion batteries, and achieved efficient sodium ion storage and electrochemical performance improvement.

CN119695105AActive Publication Date: 2025-03-25ZHEJIANG SCI-TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411850179.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

As the negative electrode material of sodium ion battery, nickel disulfide has low electron conductivity, easy agglomeration and serious volume changes in electrochemical processes, which limits its development and application in sodium ion battery.

Method used

Nickel disulfide/cubic sulfide/carbon composite hollow spheres were prepared by synthesizing hollow spherical Ni-MOF by simple solvothermal method as the precursor, and combined with ion exchange, dopamine hydrochloride and glucose bilayer coating, carbonization and vulcanization. This method retains the porous hollow structure of Ni-MOF, alleviates volume expansion and contraction, and improves conductivity and structural stability through the introduction of copper ions and double-layer carbon coating.

Benefits of technology

The prepared nickel disulfide/cubic sulfide/carbon composite hollow sphere material can effectively alleviate volume changes, improve the cycle life of sodium ion batteries, and significantly improve the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695105A_ABST
    Figure CN119695105A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a preparation method and application of nickel disulfide / copper sulfide / carbon composite hollow spheres. The nickel disulfide / copper sulfide / carbon composite hollow sphere is prepared by taking hollow spherical Ni-MOF as a precursor and combining subsequent ion exchange, PDA coating, glucose coating, carbonization and vulcanization. The material inherits a Ni-MOF porous hollow structure, a high-speed effective transmission channel can be provided for ion diffusion in an electrode material, meanwhile, the volume change effect is relieved, and the cycle life of a sodium ion battery is prolonged. In addition, a proper amount of copper ions are controllably introduced through ion exchange to form a nickel-copper bimetallic sulfide heterostructure, so that ion diffusion kinetics can be accelerated, ion diffusion barriers can be reduced, and structural stability can be enhanced. Finally, the conductivity of the composite material is improved through nitrogen-doped carbon derived from carbonization of polydopamine in the middle layer, sodium storage active sites are increased, and the structural stability of the composite material is further enhanced through a carbon layer derived from carbonization of glucose in the outermost layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and more specifically relates to a preparation method and application of nickel disulfide / copper sulfide / carbon composite hollow spheres. Background Art

[0002] Sodium-ion batteries are considered to be one of the candidates for the next generation of large-scale energy storage devices due to their abundant sodium resources, low cost and high safety. The electrochemical performance of sodium-ion batteries depends largely on the choice of electrode materials. + Due to its large ionic radius, it cannot be effectively embedded in commercial lithium battery negative electrode materials such as graphite. Therefore, it is urgent to develop sodium storage negative electrode materials with high specific capacity, high rate and long cycle life.

[0003] Nickel disulfide has a high theoretical specific capacity (870 mAh g -1 ) and a relatively low voltage platform, making it a very promising negative electrode material for sodium-ion batteries. However, the low electronic conductivity of nickel disulfide, easy agglomeration during the preparation process, and severe volume changes during the electrochemical process have hindered its further development and application in sodium-ion batteries.

[0004] In response to the above problems, researchers have mainly adopted the following strategies for improvement: (1) material nano-design (such as quantum dots, nanowires, nanosheets, etc.); (2) composite with materials with good conductivity (such as graphene, carbon nanotubes, etc.); (3) constructing bimetallic sulfide heterojunctions. Among them, constructing a heterostructure is a strategy with outstanding advantages. The heterostructure composed of different materials not only combines the energy storage advantages of two or more materials, but also forms abundant defects at the heterogeneous interface, which is conducive to increasing the Na + Storage sites. In addition, the built-in electric field spontaneously formed at the heterojunction interface also plays a positive role in enhancing the kinetics of the sodium storage reaction. Rationally designed and prepared heterojunctions can maximize the advantages of different component materials, but the preparation methods of heterojunctions are often very complex and difficult to control.

[0005] The existing invention patent CN116588974A discloses a NiS2 / MoS2 / C composite negative electrode material for sodium ion batteries. The preparation method of the composite material includes: (1) mixing nickel salt and complexing agent, and preparing a carbon framework composite material by hard template method; (2) mixing the carbon framework composite material, ammonium heptamolybdate and thiourea, and preparing carbon-supported MoS2 through hydrothermal reaction. x Nanosheet composites; (3) Under the action of a sulfurizing agent, carbon-supported MoS xThe nanosheet composite material is calcined to obtain a carbon-supported MoS2 nanosheet and NiS2 nanocrystal composite material. The obtained composite material has a lamellar structure, which effectively buffers the volume expansion of the negative electrode material during the sodium storage reaction and promotes the rapid transfer of electrons / ions. However, the preparation process of this method is relatively complicated, and the ratio of the two metal ions cannot be accurately controlled; and molybdenum is a rare metal in the raw material, which makes the raw material cost relatively high. Summary of the invention

[0006] In view of the shortcomings and problems existing in the prior art, the present invention provides a method for preparing nickel disulfide / copper sulfide / carbon composite hollow spheres and their application. The present invention uses hollow spherical Ni-MOF synthesized by a simple solvent thermal method as a precursor, and combines ion exchange, dopamine hydrochloride (PDA) and glucose double layer coating, carbonization and sulfurization to prepare nickel disulfide / copper sulfide / carbon composite hollow spheres. The prepared nickel disulfide / copper sulfide / carbon composite hollow sphere composite material inherits the porous hollow structure of Ni-MOF, which can be used as the Na in electrode materials. + Ion diffusion provides a high-speed and efficient transmission channel, while alleviating volume expansion and contraction, and improving the cycle life of sodium-ion batteries. In addition, the controllable introduction of an appropriate amount of copper ions through ion exchange to form a nickel-copper bimetallic sulfide heterostructure can accelerate ion diffusion kinetics, reduce ion diffusion barriers, and enhance structural stability; finally, the nitrogen-doped carbon derived from the carbonization of polydopamine in the middle layer improves the conductivity of the composite material and increases the sodium storage active sites, and the carbon layer derived from the carbonization of glucose in the outermost layer further enhances the structural stability of the composite material.

[0007] In order to achieve the above object, the present invention is implemented by the following technical scheme: a method for preparing nickel disulfide / copper sulfide / carbon composite hollow spheres, comprising the following steps:

[0008] (1) nickel salt, organic ligand trimesic acid, and surfactant are mixed and dissolved in a solvent, stirred, and transferred to a reactor for solvent thermal reaction to obtain Ni-MOF hollow spheres.

[0009] (2) Ni-MOF hollow spheres and copper salt are mixed and dispersed in a solvent, stirred, and centrifuged to obtain CuNi-MOF.

[0010] (3) Dispersing CuNi-MOF in a buffer solution, then adding dopamine hydrochloride, stirring at room temperature, and centrifuging to obtain CuNi-MOF / PDA.

[0011] (4) Dispersing CuNi-MOF / PDA in a solvent, then adding glucose, stirring and transferring to a reactor, and obtaining CuNi-MOF / PDA / C6H 12 O6.

[0012] (5) Put CuNi-MOF / PDA / C6H 12 O6 was calcined under inert gas protection to obtain CuNi / NC / C hollow spheres.

[0013] (6) The CuNi / NC / C hollow spheres are gas-phase sulfurized to obtain nickel disulfide / copper sulfide / carbon composite hollow spheres.

[0014] In the above preparation process, the present invention first uses the hollow spherical Ni-MOF synthesized by a simple solvothermal method as a precursor, and combines ion exchange, dopamine hydrochloride and glucose double-layer coating, carbonization and sulfurization to prepare nickel disulfide / copper sulfide / carbon composite hollow spheres. The nickel disulfide / copper sulfide / carbon composite hollow sphere composite material prepared by this method inherits the porous hollow structure of Ni-MOF and can be used as the Na in the electrode material. + Ion diffusion provides a high-speed and efficient transmission channel, while alleviating volume expansion and contraction, and improving the cycle life of sodium-ion batteries. In addition, the controllable introduction of an appropriate amount of copper ions through ion exchange to form a nickel-copper bimetallic sulfide heterostructure can accelerate the ion diffusion kinetics, reduce the ion diffusion barrier, and enhance the structural stability; finally, the nitrogen-doped carbon derived from the carbonization of the middle layer of polydopamine improves the conductivity of the composite material and increases the sodium storage active sites, and the carbon layer derived from the carbonization of the outermost layer of glucose further enhances the structural stability of the composite material. The biggest advantage of polydopamine coating is that it can self-aggregate on the surface of almost any material, so it can be used for uniform coating of CuNi-MOF. However, the coating environment must be weakly alkaline, so the coating of glucose must be after the coating of polydopamine to avoid the influence of the weakly alkaline environment on glucose.

[0015] Preferably, in step (2), the mass ratio of the Ni-MOF hollow spheres to the copper salt is 1:(2-7).

[0016] The present invention finds that the mass ratio of Ni-MOF hollow spheres to copper salt is important for the performance of the final product. During the ion exchange process, if the Cu ion concentration is too high, the ion exchange will be too intense, which will in turn destroy the Ni-MOF structure; conversely, if the Cu ion concentration is too low, less Cu ions will be introduced, and the constructed heterogeneous structure will have little effect on the performance of the material.

[0017] Preferably, in step (3), the mass ratio of the CuNi-MOF to dopamine hydrochloride is 1:(5-10).

[0018] The present invention finds that the mass ratio of CuNi-MOF to dopamine hydrochloride is important for the performance of the final product. If the amount of dopamine hydrochloride is too high, the carbon layer will be too thick, affecting the electrochemical performance of the material. The reason is that although the thicker inner layer of carbon can better alleviate the volume expansion of the material, its increased density leads to reduced sodium ion transmission performance; on the contrary, if the amount of dopamine hydrochloride is too low, the carbon coating will be uneven.

[0019] Preferably, in step (4), the mass ratio of CuNi-MOF / PDA to glucose is 1:(10-30)

[0020] The present invention found that the quality of CuNi-MOF / PDA and glucose is more important for the performance of the final product. If the amount of glucose is too high, part of the glucose will agglomerate together, making the carbon content of the composite material too high, thereby reducing the capacity of the composite material; conversely, if the amount of glucose is too low, it will lead to uneven carbon coating.

[0021] Preferably, in step (1), the mass ratio of the nickel salt, the organic ligand and the surfactant is 1:(0.3-0.5):(2-6).

[0022] Preferably, the surfactant is polyvinyl pyrrolidone; and the nickel salt is nickel nitrate hexahydrate, nickel sulfate heptahydrate or nickel chloride.

[0023] Preferably, in step (1), the solvent is a mixed solution of water / anhydrous ethanol / N,N-dimethylformamide in a volume ratio of 1:(0.8-1.2):(0.8-1.2).

[0024] Preferably, in step (1), the solvent thermal conditions are: reacting at a temperature of 130 to 170° C. for 10 to 16 hours.

[0025] Preferably, in step (2), the copper salt is copper sulfate pentahydrate, copper nitrate trihydrate or copper chloride.

[0026] Preferably, in step (2), the solvent is methanol, anhydrous ethanol or N,N-dimethylformamide.

[0027] Preferably, in step (3), the solvent is ethylene glycol or N,N-dimethylformamide.

[0028] Preferably, in step (3), the solvent thermal conditions are: reacting at a temperature of 130 to 170° C. for 5 to 10 hours.

[0029] Preferably, in step (4), the calcination conditions are: in a nitrogen or argon atmosphere, heating to 400-600° C. at a heating rate of 2-5° C. / min and calcining for 1-3 h.

[0030] Preferably, in step (6), the conditions for the gas phase vulcanization are: the mass ratio of CuNi / NC / C hollow spheres to sulfur powder is 1:(3-6), the vulcanization temperature is 300-500°C, and the heating rate is 2-5°C.

[0031] The present invention also provides the use of nickel disulfide / copper sulfide / carbon composite hollow spheres obtained by the above preparation method as negative electrode materials for sodium ion batteries.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] (1) The present invention obtains hollow spherical Ni-MOF by a simple solvothermal method, which has a simple preparation method, mild reaction conditions, and controllable morphology and size.

[0034] (2) The nickel disulfide / copper sulfide / carbon composite hollow spheres prepared by the present invention better retain the unique hollow spherical structure of the precursor, which can alleviate the volume change of the electrode material during the charge and discharge process.

[0035] (3) The present invention controllably introduces an appropriate amount of copper ions through ion exchange to form a nickel-copper bimetallic sulfide heterostructure, forming a uniform heterogeneous interface between the two-phase components, which can accelerate the ion diffusion kinetics, reduce the ion diffusion barrier, and significantly improve the electrochemical performance.

[0036] (4) The nickel disulfide / copper sulfide / carbon composite hollow sphere prepared by the present invention contains a double-layer carbon material, wherein the nitrogen-doped carbon derived from the carbonization of polydopamine in the middle layer can improve the conductivity of the composite material and increase the sodium storage active sites, and the carbon layer derived from the carbonization of glucose in the outermost layer can further enhance the structural stability of the composite material.

[0037] (5) The present invention combines multiple means to alleviate the volume effect of metal sulfides during the charge and discharge process and improve their conductivity, so that the composite material has good electrochemical properties as a negative electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a scanning electron microscope image of Ni-MOF in Example 1 of the present invention;

[0039] Figure 2 is the X-ray powder diffraction pattern of Ni-MOF in Example 1 of the present invention;

[0040] Figure 3 is an X-ray powder diffraction pattern of nickel disulfide / copper sulfide / carbon composite hollow spheres in Example 1 of the present invention;

[0041] Figure 4 This is a scanning electron microscope image of the nickel disulfide / copper sulfide / carbon composite hollow sphere in Example 1 of the present invention;

[0042] Figure 5 is a scanning electron microscope image of the nickel disulfide / copper sulfide / carbon composite hollow sphere in Example 2 of the present invention;

[0043] Figure 6 is a scanning electron microscope image of the nickel disulfide / copper sulfide / carbon composite hollow sphere in Example 3 of the present invention;

[0044] Figure 7 The sample in Example 1 of the present invention is 1Ag -1 The cycle performance diagram below. DETAILED DESCRIPTION

[0045] The technical content and effects of the present invention are further described in detail below in conjunction with the embodiments, but the present invention is not limited thereto.

[0046] Example 1

[0047] (1) 864 mg of nickel sulfate, 300 mg of organic ligand (trimellitic acid) and 3 g of polyvinylpyrrolidone K-30 were dissolved in 60 mL of a mixed solvent (deionized water: anhydrous ethanol: N,N-dimethylformamide = 1:1:1, V / V / V) and magnetically stirred for 60 min. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 160 °C for 16 h. The reaction was cooled to room temperature, and the product was centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol and dried in vacuo to obtain hollow spherical Ni-MOF.

[0048] (2) The hollow spherical Ni-MOF obtained in step 1 and 1 mmol of copper salt (copper chloride) were dispersed and dissolved in methanol, stirred for 4 h, and then centrifuged and dried to obtain CuNi-MOF.

[0049] (3) The CuNi-MOF obtained in step 2 was dispersed in 100 ml of buffer, and then 1 g of dopamine hydrochloride was added, stirred at room temperature for 6 h, and centrifuged to obtain CuNi-MOF / PDA.

[0050] (4) The CuNi-MOF / PDA obtained in step 3 and 1 g of glucose were dispersed and dissolved in N,N-dimethylformamide, then transferred to a reactor and kept at 160 °C for 10 h to obtain CuNi-MOF / PDA / C6H 12 O6.

[0051] (5) The CuNi-MOF / PDA / C6H obtained in step 3 12 O6 was heated to 600 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and kept at this temperature for 2 h to obtain CuNi / NC / C hollow spheres.

[0052] (6) The CuNi / NC / C hollow spheres obtained in step 4 and sulfur powder were placed on both sides of a quartz boat in a mass ratio of 1:4, and sealed with aluminum foil. The boat was heated to 500°C at a heating rate of 2°C / min in a nitrogen atmosphere and kept warm for 2 h to obtain nickel disulfide / copper sulfide / carbon composite hollow spheres.

[0053] Example 2

[0054] (1) 864 mg of nickel sulfate, 300 mg of organic ligand (trimellitic acid) and 3 g of polyvinylpyrrolidone K-30 were dissolved in 60 mL of a mixed solvent (deionized water: anhydrous ethanol: N,N-dimethylformamide = 1:1:1, V / V / V) and magnetically stirred for 60 min. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 160 °C for 16 h. The reaction was cooled to room temperature, and the product was centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol and dried in vacuo to obtain hollow spherical Ni-MOF.

[0055] (2) The hollow spherical Ni-MOF obtained in step 1 and 2 mmol of copper salt (copper nitrate trihydrate) were dispersed and dissolved in methanol, stirred for 4 h, and then centrifuged and dried to obtain CuNi-MOF.

[0056] (3) The CuNi-MOF obtained in step 2 was dispersed in 100 ml of buffer, and then 1 g of dopamine hydrochloride was added, stirred at room temperature for 6 h, and centrifuged to obtain CuNi-MOF / PDA.

[0057] (4) The CuNi-MOF / PDA obtained in step 3 and 1 g of glucose were dispersed and dissolved in N,N-dimethylformamide, then transferred to a reactor and kept at 160 °C for 10 h to obtain CuNi-MOF / PDA / C6H 12 O6.

[0058] (5) The CuNi-MOF / PDA / C6H obtained in step 3 12 O6 was heated to 600 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and kept at this temperature for 2 h to obtain CuNi / NC / C hollow spheres.

[0059] (6) The CuNi / NC / C hollow spheres obtained in step 4 and sulfur powder were placed on both sides of a quartz boat in a mass ratio of 1:4, and sealed with aluminum foil. The boat was heated to 500°C at a heating rate of 2°C / min in a nitrogen atmosphere and kept warm for 2 h to obtain nickel disulfide / copper sulfide / carbon composite hollow spheres.

[0060] Example 3

[0061] (1) 864 mg of nickel sulfate, 300 mg of organic ligand (trimellitic acid) and 3 g of polyvinylpyrrolidone K-30 were dissolved in 60 mL of a mixed solvent (deionized water: anhydrous ethanol: N,N-dimethylformamide = 1:1:1, V / V / V) and magnetically stirred for 60 min. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 160 °C for 16 h. The reaction was cooled to room temperature, and the product was centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol and dried in vacuo to obtain hollow spherical Ni-MOF.

[0062] (2) The hollow spherical Ni-MOF obtained in step 1 and 1 mmol of copper salt (copper sulfate pentahydrate) were dispersed and dissolved in methanol, stirred for 4 h, and then centrifuged and dried to obtain CuNi-MOF.

[0063] (3) The CuNi-MOF obtained in step 2 was dispersed in 100 ml of buffer, and then 1 g of dopamine hydrochloride was added, stirred at room temperature for 6 h, and centrifuged to obtain CuNi-MOF / PDA.

[0064] (4) The CuNi-MOF / PDA obtained in step 3 and 2 g of glucose were dispersed and dissolved in N,N-dimethylformamide, then transferred to a reactor and kept at 160 °C for 10 h to obtain CuNi-MOF / PDA / C6H 12 O6.

[0065] (5) The CuNi-MOF / PDA / C6H obtained in step 3 12 O6 was heated to 600 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and kept at this temperature for 2 h to obtain CuNi / NC / C hollow spheres.

[0066] (6) The CuNi / NC / C hollow spheres obtained in step 4 and sulfur powder were placed on both sides of a quartz boat in a mass ratio of 1:4, and sealed with aluminum foil. The boat was heated to 500°C at a heating rate of 2°C / min in a nitrogen atmosphere and kept warm for 2 h to obtain nickel disulfide / copper sulfide / carbon composite hollow spheres.

[0067] Comparative Example 1

[0068] (1) 864 mg of nickel sulfate, 300 mg of organic ligand (trimellitic acid) and 3 g of polyvinylpyrrolidone K-30 were dissolved in 60 mL of a mixed solvent (deionized water: anhydrous ethanol: N,N-dimethylformamide = 1:1:1, V / V / V) and magnetically stirred for 60 min. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 160 °C for 16 h. The reaction was cooled to room temperature, and the product was centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol and dried in vacuo to obtain hollow spherical Ni-MOF.

[0069] (2) The Ni-MOF obtained in step 1 was heated to 600°C at a heating rate of 2°C / min under a nitrogen atmosphere, and kept at this temperature for 2 h to obtain Ni hollow spheres.

[0070] (3) The Ni / C hollow spheres and sulfur powder obtained in step 2 were placed on both sides of a quartz boat in a mass ratio of 1:4, and sealed with aluminum foil. The boat was heated to 500°C at a heating rate of 2°C / min in a nitrogen atmosphere and kept warm for 2 h to obtain nickel disulfide hollow spheres.

[0071] Comparative Example 2

[0072] (1) 864 mg of nickel sulfate, 300 mg of organic ligand (trimellitic acid) and 3 g of polyvinylpyrrolidone K-30 were dissolved in 60 mL of a mixed solvent (deionized water: anhydrous ethanol: N,N-dimethylformamide = 1:1:1, V / V / V) and magnetically stirred for 60 min. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 160 °C for 16 h. The reaction was cooled to room temperature, and the product was centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol and dried in vacuo to obtain hollow spherical Ni-MOF.

[0073] (2) The Ni-MOF obtained in step 1 was dispersed in 100 ml of buffer, and then 1 g of dopamine hydrochloride was added, stirred at room temperature for 6 h, and centrifuged to obtain Ni-MOF / PDA.

[0074] (3) The Ni-MOF / PDA obtained in step 2 and 1 g of glucose were dispersed and dissolved in N,N-dimethylformamide, then transferred to a reactor and kept at 160 °C for 10 h to obtain Ni-MOF / PDA / C6H 12 O6.

[0075] (4) Ni-MOF / PDA / C6H obtained in step 3 12 O6 was heated to 600 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and kept at this temperature for 2 h to obtain Ni / NC / C hollow spheres.

[0076] (5) The Ni / NC / C hollow spheres and sulfur powder obtained in step 4 were placed on both sides of a quartz boat in a mass ratio of 1:4, and sealed with aluminum foil. In a nitrogen atmosphere, the temperature was increased to 500°C at a heating rate of 2°C / min and kept at this temperature for 2 h to obtain nickel disulfide / carbon composite hollow spheres.

[0077] Comparative Example 3

[0078] (1) Disperse 1 mmol of copper salt (copper chloride) in 100 ml of buffer, then add 1 g of dopamine hydrochloride, stir at room temperature for 6 h, and finally add 1 g of glucose. Transfer the mixture to a reactor and keep it at 160 °C for 10 h to obtain a precursor.

[0079] (2) The precursor obtained in step 1 was heated to 600°C at a heating rate of 2°C / min under a nitrogen atmosphere, and kept at this temperature for 2 h to obtain Cu / NC / .

[0080] (3) The Cu / NC / C and sulfur powder obtained in step 2 were placed on both sides of a quartz boat in a mass ratio of 1:4, and sealed with aluminum foil. In a nitrogen atmosphere, the temperature was increased to 500°C at a heating rate of 2°C / min and kept at this temperature for 2 h to obtain a copper sulfide / carbon composite material.

[0081] Comparative Example 4

[0082] (1) 864 mg of nickel sulfate, 300 mg of organic ligand (trimellitic acid) and 3 g of polyvinylpyrrolidone K-30 were dissolved in 60 mL of a mixed solvent (deionized water: anhydrous ethanol: N,N-dimethylformamide = 1:1:1, V / V / V) and magnetically stirred for 60 min. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 160 °C for 16 h. The reaction was cooled to room temperature, and the product was centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol and dried in vacuo to obtain hollow spherical Ni-MOF.

[0083] (2) The hollow spherical Ni-MOF obtained in step 1 and 1 mmol of copper salt (copper chloride) were dispersed and dissolved in methanol, stirred for 4 h, and then centrifuged and dried to obtain CuNi-MOF.

[0084] (3) The CuNi-MOF obtained in step 2 and 1 g of glucose were dispersed and dissolved in N,N-dimethylformamide, then transferred to a reactor and kept at 160 °C for 10 h to obtain CuNi-MOF / C6H 12 O6.

[0085] (4) The CuNi-MOF / C6H obtained in step 3 12 O6 was heated to 600°C at a heating rate of 2°C / min in a nitrogen atmosphere and kept at this temperature for 2 h to obtain CuNi / C hollow spheres.

[0086] (5) The CuNi / C hollow spheres obtained in step 4 and sulfur powder were placed on both sides of a quartz boat in a mass ratio of 1:4, and sealed with aluminum foil. The boat was heated to 500°C at a heating rate of 2°C / min in a nitrogen atmosphere and kept warm for 2 h to obtain nickel disulfide / copper sulfide / carbon composite hollow spheres.

[0087] Comparative Example 5

[0088] (1) 864 mg of nickel sulfate, 300 mg of organic ligand (trimellitic acid) and 3 g of polyvinylpyrrolidone K-30 were dissolved in 60 mL of a mixed solvent (deionized water: anhydrous ethanol: N,N-dimethylformamide = 1:1:1, V / V / V) and magnetically stirred for 60 min. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 160 °C for 16 h. The reaction was cooled to room temperature, and the product was centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol and dried in vacuo to obtain hollow spherical Ni-MOF.

[0089] (2) The hollow spherical Ni-MOF obtained in step 1 and 1 mmol of copper salt (copper nitrate trihydrate) were dispersed and dissolved in methanol, stirred for 4 h, and then centrifuged and dried to obtain CuNi-MOF.

[0090] (3) The CuNi-MOF obtained in step 2 was dispersed in 100 ml of buffer, and then 1 g of dopamine hydrochloride was added, stirred at room temperature for 6 h, and centrifuged to obtain CuNi-MOF / PDA.

[0091] (4) The CuNi-MOF / PDA obtained in step 3 was heated to 600°C at a heating rate of 2°C / min under a nitrogen atmosphere, and kept at this temperature for 2 h to obtain CuNi / NC hollow spheres.

[0092] (5) The CuNi / NC hollow spheres and sulfur powder obtained in step 4 were placed on both sides of a quartz boat in a mass ratio of 1:4, and sealed with aluminum foil. The boat was heated to 500°C at a heating rate of 2°C / min in a nitrogen atmosphere and kept warm for 2 h to obtain nickel disulfide / copper sulfide / carbon composite hollow spheres.

[0093] Performance Testing

[0094] The final products obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were mixed with a conductive agent Super P, a binder polyvinylidene fluoride and a solvent N-methylpyrrolidone in a mass ratio of 7:2:1 to prepare a homogeneous slurry, which was applied on a copper current collector. After drying, it was punched into discs with a diameter of 12 mm as the negative electrode, metallic sodium was used as the counter electrode, 1M sodium hexafluorophosphate (NaPF6) dissolved in diethylene glycol dimethyl ether was used as the electrolyte, and glass fiber was used as the diaphragm. The CR2025 button batteries were assembled in a glove box filled with argon atmosphere and with a water oxygen value of less than 0.01ppm. After being left for 24 hours, a constant current charge and discharge test was performed in the range of 0.01 to 3V using a Xinwei tester.

[0095] Figure 1 The SEM images of the Ni-MOF prepared in Examples 1 to 3 show that the prepared Ni-MOF is a regular hollow sphere structure with a size of about 3 μm.

[0096] Figure 2 : XRD patterns of Ni-MOF prepared in Examples 1 to 3.

[0097] Figure 3 is the X-ray powder diffraction pattern of nickel disulfide / copper sulfide / carbon composite hollow spheres in Example 1, from Figure 3 It can be seen that the nickel disulfide / copper sulfide / carbon composite hollow spheres prepared in Example 1 show characteristic peaks of NiS2 and CuS.

[0098] Figure 4 This is a SEM image of the nickel disulfide / copper sulfide / carbon composite hollow sphere in Example 1. It can be seen that the composite material has a regular hollow sphere structure with a size of about 3 μm.

[0099] Figure 5 This is the SEM image of the nickel disulfide / copper sulfide / carbon composite hollow sphere in Example 2. It can be seen that the structure of the hollow sphere is mostly destroyed. It may be that the copper ion concentration is too high during the ion exchange process, and the ion exchange is too intense, resulting in the destruction of the Ni-MOF structure.

[0100] Figure 6 This is the SEM image of the nickel disulfide / copper sulfide / carbon composite hollow sphere in Example 3. It can be seen that there are many irregular block-like substances agglomerated together. It may be that there is too much glucose, and part of the glucose is agglomerated together, and many irregularly shaped carbon blocks are generated after carbonization.

[0101] Figure 7 The cycle performance diagram of Example 1 shows that the sodium ion battery has a cycle performance of 1Ag. -1 After 100 cycles at a current density of 1.34 W, the capacity remained at 810 mAh g -1 , the capacity retention rate is 100.1%, indicating that the composite material has excellent cycle stability.

[0102] The products obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were used as negative electrode materials for sodium ion batteries and assembled into sodium ion cells. -1 The specific capacity and retention rate after 100 cycles at a current density of are shown in Table 1.

[0103] Table 1

[0104]

[0105] As shown in Table 1, it can be seen from the data of Examples 1 to 3 and Comparative Examples 1 to 5 that the controllable introduction of an appropriate amount of copper ions through ion exchange to construct a nickel-copper bimetallic sulfide heterostructure and an additional double-layer carbon coating can effectively improve the reversible capacity and cycle stability of the material. It can be seen from Example 1 and Example 2 that excessive ion exchange will destroy the original hollow sphere morphology, thereby affecting its sodium storage performance. It can be seen from Example 1 and Example 3 that too much glucose will cause the carbon content in the composite material to be too high, thereby affecting its sodium storage performance. It can be seen from Example 1 and Comparative Examples 4 to 5 that compared with single-layer carbon coating, double-layer carbon coating can better improve the conductivity and structural stability of the material, thereby improving the cycle performance of the material.

[0106] The above embodiments of the present invention are merely examples for illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing nickel disulfide / copper sulfide / carbon composite hollow spheres, characterized in that The following steps are involved: (1) nickel salt, organic ligand trimesic acid, and surfactant are mixed and dissolved in a solvent, and a solvothermal reaction is performed to obtain Ni-MOF hollow spheres; (2) mixing and dispersing Ni-MOF hollow spheres and copper salt in a solvent, stirring for reaction, and centrifuging to obtain CuNi-MOF; the mass ratio of Ni-MOF hollow spheres to copper salt is 1:(2-7); (3) Dispersing CuNi-MOF in a buffer solution, adding dopamine hydrochloride (PDA), stirring for reaction, centrifuging to obtain CuNi-MOF / PDA; the mass ratio of CuNi-MOF to dopamine hydrochloride is 1:(5-10); (4) Dispersing CuNi-MOF / PDA in a solvent, adding glucose, stirring and performing a solvothermal reaction to obtain CuNi-MOF / PDA / C6H 12 O6; the mass ratio of CuNi-MOF / PDA to glucose is 1:(10-30); (5) Put CuNi-MOF / PDA / C6H 12 O6 was calcined under inert gas protection to obtain CuNi / NC / C hollow spheres; (6) The CuNi / NC / C hollow spheres are gas-phase sulfurized to obtain nickel disulfide / copper sulfide / carbon composite hollow spheres.

2. The preparation method according to claim 1, characterized in that In step (1), The mass ratio of the nickel salt, the organic ligand and the surfactant is 1:(0.3-0.5):(2-6); The surfactant is polyvinyl pyrrolidone; The nickel salt is nickel nitrate hexahydrate, nickel chloride or nickel sulfate heptahydrate.

3. The preparation method according to claim 1, characterized in that: In step (1), the solvent is a mixed solution of water, anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:(0.8-1.2):(0.8-1.2).

4. The preparation method according to claim 1, characterized in that: In step (1), the solvent thermal reaction conditions are: reaction at 130-170° C. for 10-16 hours.

5. The preparation method according to claim 1, characterized in that: In step (2), The copper salt is copper sulfate pentahydrate, copper nitrate trihydrate or copper chloride; The solvent is methanol, anhydrous ethanol or N,N-dimethylformamide.

6. The preparation method according to claim 1, characterized in that: In step (3), the solvent is ethylene glycol or N,N-dimethylformamide.

7. The preparation method according to claim 1, characterized in that: In step (3), the solvent thermal reaction conditions are: reacting at 130-170° C. for 5-10 hours.

8. The preparation method according to claim 1, characterized in that: In step (4), the calcination conditions are: in a nitrogen or argon atmosphere, the temperature is increased to 400-600° C. at a heating rate of 2-5° C. / min and calcined for 1-3 hours.

9. The preparation method according to claim 1, characterized in that: In step (6), the conditions for the gas phase vulcanization are: the mass ratio of CuNi / NC / C hollow spheres to sulfur powder is 1:(3-6), the vulcanization temperature is 300-500°C, and the heating rate is 2-5°C.

10. Use of nickel disulfide / copper sulfide / carbon composite hollow spheres prepared by the preparation method according to any one of claims 1 to 9 as negative electrode materials for sodium ion batteries.

Citation Information

Patent Citations

  • Carbon-supported molybdenum sulfide nanosheet and nickel sulfide nanocrystalline composite material, preparation and application

    CN116588974A

  • Disulfide composite material as well as preparation method and application thereof

    CN112958118A

  • Nickel disulfide / cobalt disulfide / nitrogen-carbon composite material as well as preparation method and application thereof

    CN116169270A

  • Preparation method and application of hollow-structure zinc-nickel sulfide carbon composite material

    CN118016856A

  • Preparation method of battery negative electrode material and sodium ion battery

    CN118431432A